SP0031 Genetic studies in familial ankylosing spondylitis: the north american spondylitis consortium experience. (1st June 2001) - Reveille, JD; Bruckel, J; Inman, R; Weisman, M; Khan, MA; Yu, DTK; Schumacher, R; Mahowald, M; Sawitzke, A; Stone, M; Vasey, F; Akey, J; et al.
Abstract : Recent genome-wide screens of English families multiplex for ankylosing spondylitis (AS) have suggested genes additional to HLA-B27 to be involved in disease susceptibility, particularly on chromosome 2q and 16q. Another recent study has suggested an association of AS with an allele of the IL-1 receptor antagonist gene (IL-1RA) on chromosome 2q. In order to confirm these findings in an independent group of families, 92 sib pairs concordant for AS by modified New York criteria from 74 North American families from the were examined with eight polymorphic microsatellite markers within the major histocompatibility complex (MHC) and HLA-DRB1, DQA1, DQB1 alleles; four markers on chromosome 2q and three on 16q near the regions previously implicated. Results for the MHC markers were as follows: No evidence of linkage was found for the markers on chromosome 2q and 16q. In addition, analysis of 29 single nucleotide polymorphisms (SNP's) from the IL-1 RA gene in 30 AS patients and 48 controls found no evidence of disease association. These data strongly suggest the presence of a second MHC gene operative in predisposition to AS at or near the HLA-DRB1 locus. Additional families are currently being studied and fine mapping studies in progress to confirm and extend these findings.